Mobbing in a non-profit organisation - Kovačič, Andrej (Organizacija (Kranj), 2017)
Purpose: The aim of this paper is to analyse mobbing in a large, non-profit, state-owned organization in order to find out to what extent mobbing is present and in what way it takes place. In addition, the purpose of the research is to analyse whether the extent of mobbing is connected to employee's age, gender and position.
Keywords: delovno okolje; medosebni odnosi; mobing; neprofitne organizacije; zaposleni